2015
DOI: 10.1186/s12903-015-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishing oral health promoting behaviours in children – parents’ views on barriers, facilitators and professional support: a qualitative study

Abstract: BackgroundThe prevention of childhood dental caries relies on adherence to key behaviours, including twice daily tooth brushing with fluoride toothpaste and reducing the consumption of sugary foods and drinks. The aim of this qualitative study was to explore parents’ perceptions of barriers and facilitators that influence these oral health behaviours in children. A further objective was to explore parents’ views on limitations and opportunities for professional support to promote children’s oral health.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
101
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(140 citation statements)
references
References 29 publications
(34 reference statements)
16
101
1
6
Order By: Relevance
“…Even so, the parents of children that had experienced caries and dental pain believed that the causes were beyond their control, due to genetics, attributed to health problems intrinsic to childhood, or just random [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Even so, the parents of children that had experienced caries and dental pain believed that the causes were beyond their control, due to genetics, attributed to health problems intrinsic to childhood, or just random [30]. …”
Section: Discussionmentioning
confidence: 99%
“…So, we hypothesise that these parents felt guilty, not because of a limited knowledge on oral health, but rather because they were probably not able to translate the knowledge (theory) that they already had on prevention into health‐promoting, preventive actions (practice). This issue has already been discussed by Duijster et al ,. who showed that when parents gain knowledge on oral health concerning their children, they are still in need of support to overcome barriers deterring them from converting this knowledge into health‐promoting behaviours.…”
Section: Discussionmentioning
confidence: 64%
“…have previously argued that the feeling of guilt in parents arises when they fear being blamed for their children's oral problems. Recently, Duijster et al . reported that parents often complain of a victim‐blaming tone when oral health advice is delivered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All children and their caregiver were given thorough oral hygiene instructions and comprehensive model explanation of horizontal scrub technique for daily oral health care (Duijster, de Jong-Lenters, Verrips, & van Loveren, 2015;Patil, Patil, & Kashetty, 2014).…”
Section: Assessment Toolsmentioning
confidence: 99%